The Impact of Cognitive Behavioral Therapy on Stress and Coping Strategies Among Parents of Deaf Children: A Field Study at the School for the Young Deaf in the Wilaya of M’sila - kharkhache, asma; bouatta, charifa (Journal of Social Sciences and Humanities, 2016)
This study aims to examine the impact of Cottraux's Cognitive Behavioral Therapy (CBT) for stress management (the independent variable) on the dependent variables: the level of perceived stress and types of coping strategies. The sample consisted of twenty fathers of deaf children attending the School for the Young Deaf in the Wilaya of M'sila between December 2013 and December 2014. Two scales were administered: the Perceived Stress Scale (PSS 14) by Cohen et al. (1988) and the Coping Strategies Scale by Paulhan et al. (1994). A pre-test, post-test, and follow-up design was employed for both the experimental group (10 fathers) and the control group (10 fathers). The results indicated a varied impact of the therapy, which comprises five components: relaxation techniques, cognitive strategies, communication skills, problem-solving strategies, and developing adaptation capacities for stressful situations. The therapeutic program effectively reduced levels of perceived stress and emotion-focused coping strategies (specifically avoidance and positive reappraisal), as well as the social support-seeking dimension of problem-focused coping. Conversely, it had no significant impact on the problem-solving dimension itself, nor on the self-blame dimension of the emotion-focused strategy.